The Correlation Of Learning Motivation With Level Of Anxiety In Remedial Exam Block Of Medicine, Malahayati University Class 2019 - Shalsabilla Suti (Jurnal KESANS : Kesehatan dan Sains, 2022)
One of the stressors for the emergence of anxiety in students is when facing exams. Anxious students often reveal that during remedial exams their memory skills are lacking, exam anxiety is influenced by two factors, namely individual and environmental factors, One of the individual factors that can affect exam anxiety is learning motivation. This study was aimed at the relationship between learning Motivation and anxiety levels in facing the Medical Block Medical Block remedial exam at Malahayati University batch 2019. The type of research used is quantitative analytical method using a cross sectional design. The sample in this study were students of the Faculty of Medicine, Malahayati University batch 2019 who took the Hematology and SSO block remedial exams. The data was obtained by filling out an exam anxiety questionnaire consisting of 10 items and learnig motivation questionnaire consisting of 35 items. The data analysis technique to test the hypothesis is Spearman Rank correlation. The results showed that most of the respondents had a low level of exam anxiety, as many as 79 people with a percentage (76.7%), with a high level of learning motivation as many as 67 people with a percentage (65%) and there was a significant relationship between learning motivation and the level of learning motivation. anxiety where the Spearman Rank correlation test obtained a significance level (p-value) of (0.033) with a correlation value of rxy = -0.210. There is a relationship between learning motivation and anxiety levels in facing the 2019 Malahayati University Medical Block remedial exam.